Feature optimization using a two-tier hybrid optimizer in an Internet of Things network - Agrawal, Akhileshwar Prasad; Singh, Nanhay (Zielona Góra: Uniwersytet Zielonogórski)
The growing use of the Internet of Things (IoT) in smart applications necessitates improved security monitoring of IoT components. The security of such components is monitored using intrusion detection systems which run machine learning (ML) algorithms to classify access attempts as anomalous or normal. However, in this case, one of the issues is the large length of the data feature vector that any ML or deep learning technique implemented on resource-constrained intelligent nodes must handle.
Keywords: IoT; anomaly mitigation; feature optimization; GWO; PSO